2022
DOI: 10.31018/jans.v14i1.3322
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic, phenotypic variability and evaluation of okra [Abelmoschus esculentus (L.) Moench] genotypes for yield components

Abstract: Okra [Abelmoschus esculentus (L.) Moench] is India's major vegetable crop, accounting for 60% of exports. Comparatively, Tamil Nadu has a small area of cultivation and production. Hence, the present study involves the utilizatization of simple measure of variability and genetic variance to develop new varieties. The experiment was conducted with 60 genotypes of okra crop using 20 quantitative traits. The analysis of variance found that genotypes were significant (P 0.05 and P 0.01) for all of the traits tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In general, shorter fruit stalk observed in amphidiploids revealed that the gene controlling this trait has been incorporated from cultivated types. A. esculentus is reported to have fruit stalk length ranging from 1.99 to 3.00 cm (Reddy et al, 2022) and that of A. caillei ranging from 1.55 to 6.11 cm (AdeOluwa and Kehinde, 2011). However, the fruit stalk length of wild species is longer, viz., A. palianus with 4 cm (Sutar et al, 2013), A. moschatus with 6.0-15.3 cm (Yadav et al, 2014;Gangopadhyay et al, 2016), and A. enbeepeegearensis with 4.3-4.5 cm (John et al, 2013c).…”
Section: Fertility Restoration In Amphidiploidsmentioning
confidence: 99%
“…In general, shorter fruit stalk observed in amphidiploids revealed that the gene controlling this trait has been incorporated from cultivated types. A. esculentus is reported to have fruit stalk length ranging from 1.99 to 3.00 cm (Reddy et al, 2022) and that of A. caillei ranging from 1.55 to 6.11 cm (AdeOluwa and Kehinde, 2011). However, the fruit stalk length of wild species is longer, viz., A. palianus with 4 cm (Sutar et al, 2013), A. moschatus with 6.0-15.3 cm (Yadav et al, 2014;Gangopadhyay et al, 2016), and A. enbeepeegearensis with 4.3-4.5 cm (John et al, 2013c).…”
Section: Fertility Restoration In Amphidiploidsmentioning
confidence: 99%